LDCs in CARICOM : a review of the special regime for CARICOM LDCs - Lestrade, Swinburne A. S. ([Caricom Secretariat] [Georgetown]GY, 1979)
Provides some background to the Special Regime and looks at critical development problems and needs in the subregion. Reviews progress under the Regime. Addresses queStions of costs and benefits, also those relating to attitudes and reactions towards CARICOM as perceived in the LDCs. Suggests modifications to the Special Regime to make it more meaningful. Makes recommendations for the more meaningful and fruitful participation of the LDCs in CARICOM.